Effort to develop young generations with high-integrity character - Dewi Fitriana; Ruaidah Ruaidah; Subhan Ajrin Sudirman (Universitas Muhammadiyah Magelang, 2023)
The low level of human resources is caused by several factors, one of which is considered quite urgent is the low fighting power of the Indonesian generation. The purpose of this community service is to provide psychoeducation regarding the understanding of what kind of parenting can support the development of grit in adolescents. The method used in this community service is service learning, which integrates academic activities into community empowerment which in turn provides opportunities for service providers to reflect on the things that have been implemented. The result of this activity is an increase in grit in students through parenting.